+0  
 
+1
53
2
avatar

Find all values of t such that \(6t - \frac23 + \frac{t}{5} = 4 + \frac{2-t}{3} \) .

If you find more than one answer, enter every answer you find as list separated by commas.

 Aug 20, 2020
 #2
avatar+110689 
+2

\(6t - \frac23 + \frac{t}{5} = 4 + \frac{2-t}{3}\)

 

The lowest common denominator is 15 so multiply both sides by 15

 

\(6t - \frac23 + \frac{t}{5} = 4 + \frac{2-t}{3}\\ 15(6t - \frac23 + \frac{t}{5}) = 15(4 + \frac{2-t}{3})\\ 90t-10+3t=60+5(2-t)\)

 

Can you take it from there?

 Aug 21, 2020

4 Online Users